2017
DOI: 10.1111/srt.12399
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurements of blood vessels’ distribution in non‐melanoma skin cancer by dynamic optical coherence tomography — a new quantitative measure?

Abstract: Background: Skin biopsies only provide point-in-time data making longitudinal studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
(50 reference statements)
0
25
0
4
Order By: Relevance
“…Therefore, an auxiliary non‐invasive diagnostic technique is needed to screen, diagnose, and monitor AK lesions. Many non‐invasive tools, such as optic coherence tomography (OCT), confocal scanning laser microscopy (CSLM), and dermoscopy, have been investigated …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an auxiliary non‐invasive diagnostic technique is needed to screen, diagnose, and monitor AK lesions. Many non‐invasive tools, such as optic coherence tomography (OCT), confocal scanning laser microscopy (CSLM), and dermoscopy, have been investigated …”
Section: Discussionmentioning
confidence: 99%
“…Many noninvasive tools, such as optic coherence tomography (OCT), confocal scanning laser microscopy (CSLM), and dermoscopy, have been investigated. [19][20][21] Thermal imaging, or IR imaging, is one of the potential diagnostic tools for the detection of cancer or precancerous lesions in dermatology. It was first introduced in skin cancer research by Brasfield et al 22 who reported that melanomas are hyperthermic compared with the surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to: detect and diagnose non-melanoma skin cancer [6], visualize the functional microvasculature of the skin [7], evaluate the oxidative effects of hair dying [8], determine the margins of basal cell carcinomas before micrographic surgery [9], and map vascularization in plaque psoriasis [10]. Quantitative uses of OCT include measurement of the surface distance to the first vessels [11], characterization of cutaneous wounds [12], thickness measurements in basal cell carcinoma and malignant melanoma [13], differentiation of benign and malignant melanoma [13] [14], and OCT capillaroscopy of nail folds [15]. Besides evaluation of skin lesion pathology, OCT has potential uses in following biofilm formation in skin wounds, biofilm associated contamination of implants and characterization of viscoelastic liquids used in surgery.…”
Section: Introductionmentioning
confidence: 99%
“…17 It can be imaged noninvasively using optical coherence tomography (OCT). [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Optical coherence tomography is a noninvasive, nondestructive optical technique for imaging tissue. It has a penetration depth of between 0.5 and 2 mm depending on the light source used and the manner in which the reflected light is analyzed.…”
mentioning
confidence: 99%
“…It has been used to detect and diagnose nonmelanoma skin cancer, 26 visualize the functional microvasculature of the skin, 19,20 evaluate the oxidative effects of hair dying, 27 follow the advancement of re-epithelization of wounds, 18 determine the margins of basal cell carcinomas before micrographic surgery, 21 do microangiography of skin, 19 and map vascularization in plaque psoriasis. 30 Quantitative uses of OCT include measurement of the surface distance to the first vessels, 29 characterization of cutaneous wounds, 22 thickness measurements in basal cell carcinoma and malignant melanoma, 23 differentiation of benign and malignant melanoma, 25 and OCT capillaroscopy of nailfolds. 31 We have developed a technique to combine OCT imaging with vibrational analysis to image and to analyze the physical properties of tissues noninvasively and nondestructively.…”
mentioning
confidence: 99%